Deformation effects in toroidal and compression dipole excitations of 170Yb: Skyrme RPA analysis - Kvasil, J.; Nesterenko, V. O.; Kleinig, W.; Reinhard, Paul-Gerhard (Physica Scripta, 2014)
The effect of nuclear deformation on the isoscalar toroidal and compression dipole modes in prolate 170Yb is studied in the framework of the random-phase-approximation method with a representative set of Skyrme forces (SV-bas, SLy6, SkMand SkI3). It is shown that the deformation crucially redistributes the strength of both modes. The compression mode has the same sequence of μ = 0 and 1 branches as the isovector giant dipole resonance where for prolate nuclei the μ = 0 mode is lower in energy (μ being the projection of the axial momentum of the mode). Instead, the toroidal mode exhibits an unexpected (opposite) sequence where the μ = 1 branch precedes the μ = 0 one. © 2014 The Royal Swedish Academy of Sciences.
CRIS-Team Scopus Importer:2023-07-24
Keywords: deformation; random-phase-approximation; toroidal and compression modes